Association between lifetime risk of atrial fibrillation and mortality in the oldest old. Issue 5 (12th May 2018) - Kheirbek, Raya Elfadel; Fokar, Ali; Moore, Hans J.; Shara, Nawar; Doukky, Rami; Fletcher, Ross D.
Abstract : Background: Age is the strongest predictor of atrial fibrillation (AF), yet little is known about AF incidence in the oldest old. Hypothesis: AF incidence declines after age 90 years, and morbidity is compressed into a brief period at the end of life. Methods: In this retrospective, longitudinal cohort study of patients (born 1905–1935), we examined cumulative lifetime incidence of AF and its impact on mortality. Data included records from 1 062 610 octogenarians, 317 161 nonagenarians, and 3572 centenarians. Kaplan–Meier curves were used to estimate cumulative incidence of AF by age group, incidence rates were compared using log‐rank tests, and Cox proportional hazards model was used to estimate unadjusted hazard ratios. The primary outcome was AF incidence at age > 80 years; the secondary outcome was mortality. Results: The cumulative AF incidence rate was 5.0% in octogenarians, 5.4% in nonagenarians, and 2.3% in centenarians. Octogenarians and nonagenarians had a higher risk of AF incidence compared to centenarians (adjusted hazard ratio 8.74, 95% confidence interval [CI]: 6.31–12.04; and 2.98, 95% CI: 2.17–4.1, respectively). The lowest hazard ratio for mortality in patients with AF compared to those without was 2.3 (95% CI: 2.3–2.4) in patients who were on antiplatelet and anticoagulant medication and had a score of 0 on the Elixhauser comorbidity index score. Conclusions: Although AF incidence increased with age, being a centenarian was associated with reduced incidence and compression of morbidity. Patients with AF had a higher adjusted mortality rate. However, data suggest that a regimen of anticoagulants and antiplatelets may reduce risk of mortality in patients over 80 with an AF diagnosis.